AGO-bound mature miRNAs are oligouridylated by TUTs and subsequently degraded by DIS3L2 - Yang, Acong; Shao, Tie-Juan; Bofill-De Ros, Xavier; Lian, Chuanjiang; Villanueva, Patricia; Dai, Lisheng; Gu, Shuo (Nature communications, 2020)
MicroRNAs (miRNAs) associated with Argonaute proteins (AGOs) regulate gene expression in mammals. miRNA 3’ ends are subject to frequent sequence modifications, which have been proposed to affect miRNA stability. However, the underlying mechanism is not well understood. Here, by genetic and biochemical studies as well as deep sequencing analyses, we find that AGO mutations disrupting miRNA 3’ binding are sufficient to trigger extensive miRNA 3’ modifications in HEK293T cells and in cancer patients. Comparing these modifications in TUT4, TUT7 and DIS3L2 knockout cells, we find that TUT7 is more robust than TUT4 in oligouridylating mature miRNAs, which in turn leads to their degradation by the DIS3L2 exonuclease. Our findings indicate a decay machinery removing AGO-associated miRNAs with an exposed 3’ end. A set of endogenous miRNAs including miR-7, miR-222 and miR-769 are targeted by this machinery presumably due to target-directed miRNA degradation. 3′ end of microRNAs binds to the PAZ domain of Argonaute (AGO) proteins. Here the authors show that terminal nucleotidyltransferases TUT4/7 and exonuclease DIS3L2 induce tailing and decay of 3’ end exposed-microRNAs in AGO PAZ mutant expressing- or cancer cells.